Anti-PD-1 Immunotherapy Combined With Stereotactic Body Radiation Therapy and GM-CSF as Salvage Therapy in a PD-L1-Positive Patient With Refractory Metastatic Thyroid Hürthle Cell Carcinoma: A Case Report and Literature Review - He, Haihua; Xu, Tangpeng; Li, Ping; Jia, Guohua; Li, Xiangpan; Song, Qibin (Frontiers in Oncology, 2021)
Thyroid Hürthle cell carcinoma, known as thyroid eosinophilic carcinoma, is a rare pathological type of differentiated thyroid cancer (DTC), representing 3-4% of all thyroid cancers. However, given the high risk of invasion and metastasis, thyroid Hürthle cell carcinoma has a relatively poor prognosis. Traditional treatment methods have limited effects on patients with metastatic thyroid cancers. Developing a valuable therapy for advanced thyroid carcinomas is an unfilled need, and immunotherapy could represent another choice for these tumors. We herein reported the case of a patient with recurrent advanced thyroid Hürthle cell cancer and positive programmed death-ligand 1 (PD-L1) expression, who suffered tumor progression after re-surgery, radiotherapy, and targeted therapy. It is encouraging that PD-1 inhibitors in combination with GM-CSF and stereotactic body irradiation (SBRT) on metastatic disease have a significant anti-tumor effect.